Separation of Powers in the Palestinian Law: Does it Reflect the Democratic System? (A Comparative Approach with Indonesia) (Universitas Negeri Semarang, 2022)
The principle of separation of powers among the three organs of government i.e., the Legislative, Executive, and Judiciary are one of the main pillars of the democratic system. This principle guarantees a balance of powers between these three organs. However, in Palestine, the issue arises as a result of a lack of commitment from these organs to practically apply this principle in accordance with the Palestinian Basic Law of 2003. Nevertheless, in Indonesian Constitution of 1945 has stated that is a democratic country with the foundation of a separation of powers. In addition, the practice in Indonesia shows that there is various constitutional mechanism to split the power. The objectives of this article are to examine the practice of separation of powers in Palestine and Indonesia and to harmonize the theoretical and practical aspects. In order to achieve these objectives, doctrinal legal research using the qualitative approach was engaged. Findings show that the principle of separation of powers was not fully practiced in Palestine between the three organs, especially the Executive and there is an absence of constitutional oversight. This article recommends that the role of the Palestinian Supreme Constitutional Court be activated to monitor all three governmental organs to ensure that this principle is fully implemented.